Analysis of Migrant Smuggling as a Transnational Organized Crime - Dioz Thimoteus Togatorop (Jurnal Ilmiah Hukum dan Hak Asasi Manusia, 2026)
Purpose: This study aims to analyze migrant smuggling as an organized transnational crime and examine law enforcement practices in Indonesia and their implications for the protection of migrants' human rights. Methodology: This study uses a normative legal research method with a statutory, conceptual, and comparative approach. Data were obtained through a literature review of national and international laws and regulations, legal doctrines, and literature related to migrant smuggling. Results: The findings indicate that migrant smuggling is a transnational organized crime involving cross-border networks. Law enforcement in Indonesia tends to focus on immigration and repressive aspects, often positioning smuggled migrants as lawbreakers rather than victims of crime. Conclusions: A law enforcement approach that is not oriented toward human rights protection has the potential to neglect migrants’ rights to liberty, personal security, and legal protection. Harmonization of criminal law and immigration policies with human rights principles and more effective international cooperation are needed. Limitations: This study is limited to normative legal analysis and does not include empirical data from field-based law enforcement practices. As a result, the findings reflect doctrinal and conceptual interpretations rather than practical implementation. The absence of empirical evidence limits a full understanding of how migrant smuggling laws are enforced in practice, thus requiring further socio-legal research. Contributions: This study contributes a conceptual framework for developing human rights-based legal policies in migrant smuggling cases, emphasizing the protection of migrants as victims of transnational organized crime.